PENERAPAN METODE NAÏVE BAYES DALAM PEMERIKSAAN KESEHATAN - Nurtriana Hidayati; Victor Gayuh Utomo; nur wakhidah (Jurnal Informatika Upgris, 2019)
Maintaining the safety and health of its workers by conducting daily health checks. The medical examination is carried out by a doctor or nurse at work. Workers who were declared unhealthy were not allowed to work on that day, in several cities, so that inspection standards were maintained, a web-based system was implemented that implemented a rule-based expert system. Naive Bayes algorithm which is included as an algorithm for classification based on data mining and machine learning activities. The initial process of Naive Bayes begins by studying existing data (complete with labels) through the training process. The results of this training are actually the probability of an outcome based on the variables used. Naive Bayes was chosen because it can study the results of past examinations and use them to make the next decision. This is felt to be a solution to the problems of previous system deficiencies that require the experience and expertise of health workers who are not necessarily equal.